Literature For Children: The Role Of Parents In Choosing Good Fairy Tales And Reading Material For Children - Girsang, Martina; Cya Aprilia S. Meliala, Grace; Ayu Br Sitepu, Eginta; Gabliela Br Gultom, Grace; Ecica Br Ginting, Wina (International Journal of Education and Digital Learning (IJEDL), 2023)
Literature is very important for our life. Literature can be enjoyed by all people, including children. There are many kinds of literature for children, namely fairy tales, folklore, children's songs, folklore, legends, and others. Literature for children is made like children's views. Imagination that emerges from children is summarized and researched into children's literature. Children's literature is made for education and as a means for children to grow to know literature. However, children need to get guidance from parents or adults in side by side with children's literature. Not all children's literature can be accepted by children. In some examples of children's literature there are things that are inappropriate for children to accept, such as fairy tales with a romantic genre. Therefore, the role of parents is important to help children get to know children's literature. Children cannot but coexist with literature. Literature for children helps children in their development. Literature for children exists so that children can express themselves as freely and as broadly as possible. Children must also accept literature and pass it on to the next generation. Without realizing it, humans live side by side with literature. Therefore, the role of parents and adults is very important in introducing literature to children.